1994
DOI: 10.1111/j.1600-0773.1994.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Mobilization by Monoaralkyl‐ and Monoalkyl Esters of meso‐2,3‐Dimercaptosuccinic Acid and by a Dithiocarbamate

Abstract: Syntheses and relative cadmium mobilizing properties are described for three new monoaralkyl esters (HOOCCH(SH)CH(SH)COOR, where R = phenylethyl ((CH2)2C6H5), MPhEDMS; R = 3-phenylpropyl ((CH2)3C6H5), MPhPDMS; and R = 2-phenoxyethyl ((CH2)2OC6H5). MPhOEDMS) of meso-2,3-dimercaptusuccinic acid. These were prepared by the reaction of the corresponding alcohol with meso-2,3-dimercaptosuccinic acid (DMSA) in aqueous HCl. When administered intraperitoneally to cadmium-loaded mice at 0.50 mmol/kg/day for four consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Compounds of this sort are designed primarily to mobilize a larger portion of intracellular cadmium via the biliary route. In a recent report from this laboratory on a structurally related compound, i.e., mono-2-phenoxyethyl meso-2,3-dimercaptosuccinate (MPhOEDMS), it was discovered that fecal excretion is the predominant route of cadmium mobilization which eliminates approximately 8-fold excess cadmium than through the urine (29). The study also revealed that the majority of cadmium excretion occurred within 5 h of the initial administration of the aforementioned compound.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds of this sort are designed primarily to mobilize a larger portion of intracellular cadmium via the biliary route. In a recent report from this laboratory on a structurally related compound, i.e., mono-2-phenoxyethyl meso-2,3-dimercaptosuccinate (MPhOEDMS), it was discovered that fecal excretion is the predominant route of cadmium mobilization which eliminates approximately 8-fold excess cadmium than through the urine (29). The study also revealed that the majority of cadmium excretion occurred within 5 h of the initial administration of the aforementioned compound.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it would probably be appropriate to conduct clinical studies to assess whether prolonged oral protocols of DMSA (or perhaps other orally administrable agents capable of chelating Cd [102]) might have a worthwhile impact on Cd body burden in patients with excessive Cd levels. Certain ester derivatives of DMSA (such as the monoisoamyl ester) have greater cell permeability, and can promote excretion of metallothionein-bound Cd in mice [103,104]; unfortunately, these agents have never been approved for clinical use, and may have more toxic potential than well-tolerated DMSA [105].…”
Section: Chelation Therapy May Have Limited Potential In Chronic Cadmmentioning
confidence: 99%
“…MPhOEDMS) of meso-2,3-dimercaptusuccinic acid have been effective in reducing the hepatic and renal Cd concentration in Cd-intoxicated rats, but no information regarding the effect of the chelating agents on the trace elements homeostasis has been presented. Furthermore, the esters of DMSA have been administrated i.p., which could be a disadvantage of these agents over others chelators for the treatment of Cd-intoxication (Table 6) [64].…”
Section: Chelating Agentsmentioning
confidence: 99%